Radical Post-Modernism and Content: Charles Jencks and Rem Koolhaas Debate the Issue - Jencks, Charles; Koolhaas, Rem (Architectural design, 2011)
The following debate took place on 28 December 2009 between Charles Jencks and Rem Koolhaas, and was transcribed and edited by Eva Branscome. Jencks and Koolhaas have exchanged ideas since the late 1960s. Jencks was the one to insist that Koolhaas come to the 1980 Venice Biennale, originally entitled ‘Post‐Modernism’. (Paolo Portoghesi invited Jencks to collaborate with him on this first Biennale before it expanded into historicism.) In January 2002, Jencks was also a judge of the competition for the CCTV Building, the headquarters for China Central Television in Beijing, discussed below. Jencks and Koolhaas continue to thrive on their discussions and disagreements. Although they have very different commitments to the issue of ‘content’, their varying positions help to clarify what is meant here by ‘radical’. Copyright © 2011 John Wiley & Sons, Ltd.